Effective time-dependent behavior of three-phase polymer matrix smart composites. (1st June 2022) - Lin, Chien-hong; Liu, Fang-Yu
Highlights: A mathematical framework is developed for modeling three-phase polymer matrix smart composites. Polymer matrix causes the effective magnetoelectric coupling to be creep due to the strain-mediated coupling between magnetostrictive and piezoelectric reinforcements. The effects of constituent, connectivity, proportion, and loading frequency on the overall time-dependent and nonlinear behavior are investigated. The 1–3 connectivity provides the best magnetoelectric coupling but at the cost of the unavoidable creep behavior. Author statement. Chien-hong Lin: Conceptualization, Funding acquisition, Methodology, Project administration, Resources, Supervision, Writing – original draft, Writing – review & editing. Fang-Yu Liu: Data curation, Formal analysis, Investigation, Software, Validation, Visualization. Abstract: This study presents a mathematical framework to predict the effective time-dependent behavior of three-phase smart composites with typical 0-3, 1-3, and 2-2 connectivities. A composite is composed of magnetostrictive and piezoelectric reinforcements that both show nonlinear multiphysics coupling and a polymer matrix that exhibits viscoelastic behavior. For dealing with nonlinear and time-dependent problems, a tangent linearization is employed to linearize the nonlinear constituents and a time-integration algorithm is applied to numerically determine the viscoelastic response of the matrix. A unified constitutive equation can be subsequently formulated to cover various phase constitutive laws following by a simplified unit-cell micromechanics model to set up a composite constitutive relation. The presented formulation is validated by limited experimental data available in literatures. Numerical results show that inclusion of a polymer matrix in a smart composite causes magnetoelectric coupling to be creep due to strain-mediated coupling among these three phases. The established unit-cell micromechanics model can be further integrated into a finite element framework to analyze composite structures, which is a great merit in a variety of practical applications. It will do so by implementing the presented micromechanics method at every integration point.